Transcriptomic and lipid profiling analysis reveals a functional interplay between testosterone and growth hormone in hypothyroid liver - Fernández-Pérez, Leandro; Guerra, Borja; Recio, Carlota; Cabrera-Galván, Juan José; García, Irma; De La Rosa, Juan Vladimir; Castrillo, Antonio; Iglesias-Gato, Diego; Díaz, Mario (Frontiers in Endocrinology, 2023)
Preclinical and clinical studies suggest that hypothyroidism might cause hepatic endocrine and metabolic disturbances with features that mimic deficiencies of testosterone and/or GH. The absence of physiological interactions between testosterone and GH can be linked to male differentiated liver diseases. Testosterone plays relevant physiological effects on somatotropic-liver axis and liver composition and the liver is a primary organ of interactions between testosterone and GH. However, testosterone exerts many effects on liver through complex and poorly understood mechanisms. Testosterone impacts liver functions by binding to the Androgen Receptor, and, indirectly, through its conversion to estradiol, and cooperation with GH. However, the role of testosterone, and its interaction with GH, in the hypothyroid liver, remains unclear. In the present work, the effects of testosterone, and how they impact on GH-regulated whole transcriptome and lipid composition in the liver, were studied in the context of adult hypothyroid-orchiectomized rats. Testosterone replacement positively modulated somatotropic-liver axis and impacted liver transcriptome involved in lipid and glucose metabolism. In addition, testosterone enhanced the effects of GH on the transcriptome linked to lipid biosynthesis, oxidation-reduction, and metabolism of unsaturated and long-chain fatty acids (FA). However, testosterone decreased the hepatic content of cholesterol esters and triacylglycerols and increased fatty acids whereas GH increased neutral lipids and decreased polar lipids. Biological network analysis of the effects of testosterone on GH-regulated transcriptome confirmed a close connection with crucial proteins involved in steroid and fatty acid metabolism. Taken together, this comprehensive analysis of gene expression and lipid profiling in hypothyroid male liver reveals a functional interplay between testosterone and pulsed GH administration.